Relationship between Spiritual Intelligence and Professional Self-concept among Iranian Nurses - Hojat , Mohsen; Badiyepeymaiejahromi, Zohreh (Investigación y Educación en Enfermería, 2021)
Objective. To determine the relationship between spiritual intelligence (SI) and professional self-concept (PSC) among Iranian nurses. Methods. This is a correlation study. A convenience sampling method was used and 344 nurses were selected from hospitals of Jahrom University of Medical Sciences. Data collection standard tools included two validated scales: Cowin’s Nurse Self-Concept Questionnaire (36 items scored ranged from 1 to 8; Maximum score=288; 6 subcategories: General Nurse Self-Concept, Knowledge, Care, Communication, Staff Relation and Leadership) and Abdollahzadeh’s SI Questionnaire (29 items scored ranged from 0 to 5; Maximum score=145; 2 subcategories: Relying on the inner core and Understanding and communicating with the origin of the universe. Results. The mean total score of PSC was 220.3±30.61 and 120.67±16.13 for SI. There was a significant statistical correlation between PSC (r=0.348, p<0.0001) and almost all subcategories and SI. The results of the regression analysis showed that SI predicts 13.3% of the variance of PSC (p<0.0001). Conclusion. Considering the correlation of SI and PSC among Iranian nurses, it is suggested that strategies be used to train and promote the SI of nurses.